Indoor air quality in passive and conventional new houses in Sweden. (November 2015) - Langer, Sarka; Bekö, Gabriel; Bloom, Erica; Widheden, Anna; Ekberg, Lars
Abstract: The indoor environment was evaluated in 20 new passive houses and 21 new conventionally built houses during the 2012/2013 and 2013/2014 heating seasons. Temperature, relative humidity (RH), the concentrations of NO2, ozone, formaldehyde, volatile organic compounds (VOC) and viable microbiological flora were measured. Air exchange rates (AER) were estimated from the CO2 concentrations measured in the bedrooms. The median AER was slightly higher in the passive houses than in the conventional ones (0.68 h −1 vs. 0.60 h −1 ). The median concentrations in the passive and the conventional buildings were 10 and 12 μg/m 3 for NO2, 9.7 and 11 μg/m 3 for ozone, 11 and 16 μg/m 3 for formaldehyde, and 270 and 150 μg/m 3 for TVOC, respectively. Significant differences in the TVOC and formaldehyde concentrations between the two groups of buildings indicated substantial sources of TVOC present in the passive houses, while sources of formaldehyde may have been more pronounced in the conventional houses. In contrast to the passive houses, the indoor microbiological flora indicated possible mould or moisture problems in six (29%) of the conventionally built houses. When compared with the results previously reported for the Swedish housing stock, AERs and NO2 concentrations were significantly higher in both groups of newly built buildings, while formaldehyde concentrations were significantly lower in the passive houses. TVOC concentrations were not significantly different from those reported for the housing stock, although the most abundant individual VOCs were present mostly at higher concentrations in the new buildings. Highlights: The indoor environment was evaluated in newly built passive and conventional houses. Median air exchange rates were above the minimum requirement by the building code. Concentrations of formaldehyde were lower in the passive houses. Concentrations of TVOC were higher in the passive houses. The results were compared to those obtained from the Swedish housing stock.